Technical efficiency and decision to exit: evidence from the dairy farms in Sukabumi district, West Java, Indonesia. (20th September 2019) - Setiawan, Maman
This research investigates technical efficiency and its effect on the decision to exit of the dairy farms in Sukabumi district, West Java, Indonesia. Farm-level data obtained from survey are used to estimate the technical efficiency using a bootstrapped data envelopment analysis. The results show that dairy farms in Sukabumi are technically inefficient. The technical efficiency also has a negative effect on the decision to exit. This implies that the dairy farms with higher technical efficiency scores tend to have lower probabilities to exit from the business.